A Note on Wavelet Estimation of the Derivatives of a Regression Function in a Random Design Setting. (3rd April 2014) - Chesneau, Christophe
Abstract : We investigate the estimation of the derivatives of a regression function in the nonparametric regression model with random design. New wavelet estimators are developed. Their performances are evaluated via the mean integrated squared error. Fast rates of convergence are obtained for a wide class of unknown functions.